The structural change of leaves in Anthurium andraeanum uder intermitten mist - Elly Kesumawati (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Photosynthesis is the fundamental basis in green plants, and the principal organ of photosynthesis is leaf. On the basis of water requirements or adaptations, as angiosperm leaves, Anthuriums require abundant soil water and relatively humid atmosphere. To identify the morphological characteristic of leaves in Anthurium, the transverses section was conducted. Two factors were tested in this experiment: 1) mist treatment (intermittent mist and control/without mist) and 2) the type of medium planting (bark and rockwool). For observation on microscopic differences, the leaves were put on the Auto Tissue Processor ROTEX and embedded the sample in a Hardener Resin (Technovit 7100), then the block-samples were sectioned in the Microtom machine at 5 um. The results of transverses section showed that the leaves of Anthurium with intermittent mist treatment, under both rock wool and bark medium thicker than control. In this experiment, the intermittent mist treatment affected the leaf structure of Anthurium andraenum. The intercellular space with connected to the outer atmosphere through the stomata was drastically increased by intermittent mist treatment which promoted transpiration, rapid gas exchange and photosynthesis.